2019
DOI: 10.3390/socsci8090265
|View full text |Cite
|
Sign up to set email alerts
|

“I Need this Chance to … Help My Family”: A Qualitative Analysis of the Aspirations of DACA Applicants

Abstract: This study explores the aspirations of undocumented youth seeking to defer deportation from the United States and obtain temporary employment authorization through Deferred Action for Childhood Arrivals (DACA). The data are twenty-three letters submitted from 2013–2015 to a nonprofit foundation in the US Southwest that provides financial assistance to pay DACA application fees. Conducted within a narrative framework, analysis of emergent themes reveals a story of hope and family that counters the dominant poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…One of these studies highlighted familial support and how it contributed to educational success (Allen-Handy & Farinde-Wu, 2018). Another study (Andrade & Lundberg, 2020) used content analysis to identify the discourse of DACA on college campuses, and others have used content analysis to examine strength, resilience (Luna & Montoya, 2019), and activism (Rodriguez et al, 2019) in the face of the negative sociopolitical climate. Specifically, content analysis describes written text by categorizing key contents into ideas rather than events (Elo & Kyngäs, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…One of these studies highlighted familial support and how it contributed to educational success (Allen-Handy & Farinde-Wu, 2018). Another study (Andrade & Lundberg, 2020) used content analysis to identify the discourse of DACA on college campuses, and others have used content analysis to examine strength, resilience (Luna & Montoya, 2019), and activism (Rodriguez et al, 2019) in the face of the negative sociopolitical climate. Specifically, content analysis describes written text by categorizing key contents into ideas rather than events (Elo & Kyngäs, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it was surprising that college dreamers who worked more and became breadwinners for their families during the pandemic did not suffer a greater mental health impact. However, it should be noted that it is common for dreamers to work while attending college (Teranishi et al, 2015) and to help their families when it comes to finances (Luna & Montoya, 2019). Therefore, to many college dreamers, contributing more to the family during the pandemic may have represented a natural extension of their pre-pandemic behavior, and thus did not signify a major source of added mental health distress.…”
Section: Employmentmentioning
confidence: 99%
“…One previous study found that students with DACA may face the decision to choose work or attend school if they attend four-year universities, but that community college students with DACA adjust the units they take to accommodate their work schedules (Hsin and Ortega 2018). Interestingly, one study found that DACA recipients framed their receipt of DACA as a way to help support their families, which they reported motivated them to continue having hope that in the future they could repay their families (Luna and Montoya 2019). We suspect that the combined pressure to work during college may add stressors to the lives of Latinx undocumented college students who may already be facing institutional contexts not conducive to seeing them thrive.…”
Section: Heterogeneity In the Undocumented Experiencementioning
confidence: 99%